Development of augmented reality to facilitate floor exercise movement skills for junior high school students - Sugiarto, Tatok; Darmawan, Arief; Sugiyanto, Sugiyanto; Priyohutomo, Ahadi; Nugroho Sigit, Cahyo (Jurnal Maenpo : Jurnal Pendidikan Jasmani Kesehatan dan Rekreasi, 2023)
Augmented reality is part of technological developments to help make interactions and learning activities more enjoyable. This research aims to develop augment reality technology to facilitate floor exercises for junior high school students. The final product in this research is an augment reality application that can be installed on a smartphone. This research and development method is adopted from Borg and Gall which is divided into 7 stages, namely the research and data collection stage, planning stage, initial product development stage, initial field trial stage, test results revision stage, field trial stage and product refinement stage , while for data collection using non-test methods (interviews, observation and documentation), and test methods. The subjects in this research involved media experts, gymnastics learning experts, and students of junior high school 1 Karangploso. The results of research on test subjects show that augmented reality floor exercise media can be implemented well with media material validation results getting an average result with a score of 88.75%, media validation getting an average result with a score of 89.75%, expert test users getting the average result was 90%, and the trial results obtained an average of 90.2%. So it can be concluded that AR (Augment Reality) technology media is suitable for use as a floor exercise lesson for Junior High School 1 Karangploso. Keyword: augment reality, floor exercise, front roll, back roll